Resposta termofílica pós-prandial do sapo-cururu, Rhinella diptycha - Clemente, Amanda Copriva [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Ectothermal animals depend primarily on behavioral adjustments coupled with the exploration of external heat sources to regulate body temperature (Tb). In addition, Tb variations can significantly affect the physiology of ectothermic organisms influencing important aspects of their reproduction, metabolism, feeding and digestion, among others. Thus, thermoregulation is a central aspect of the biology of ectothermal animals. In ectothermalvertebrates it is common for animals to have a preference for a particular temperature or temperature range, which is called the preferred body temperature (Tpref). This preference, however, can be altered in function of external factors or the condition of the animals. For example, fed animals generally exhibit an increase in Tpref - referred to a postprandial thermophilic response - which potentially improves food digestion performance. This response is relatively well documented in Squamata, but among anuran amphibians, information on its occurrence, magnitude and possible determinants is scarce. Thus, in the present study, we investigated whether the cururu toad, Rhinella diptycha, changes its thermal preference after being fed with a prey with a mass equivalent to 15% of its body mass. For this, fed and fasted animals were maintained for eight consecutive days in a thermal gradient with temperatures ranging from 15ºC to 30ºC. During this period, the Tb of the frogs was continuously monitored with temperature sensors (iButtons®) implanted intraperitoneally. The Tpref values of the fed animals increased to levels significantly higher than the Tpref values of fasted animals on the second day after feeding and that difference was maintained until the end of the experiments. The occurrence of a postprandial thermophilic response in R. diptycha indicates that this species is able to adjust its thermoregulatory behavior as a function of feed, possibly improving digestion efficiency

Animais ectotérmicos dependem primariamente de ajustes comportamentais conjugados com a exploração de fontes externas de calor para regulação da temperatura corpórea (Tc). Ademais, variações da Tc podem afetar significativamente a fisiologia dos organismos ectotérmicos influenciando aspectos importantes de sua reprodução, metabolismo, alimentação e digestão, entre outros. Assim, a termorregulação constitui um aspecto central da biologia dos animais ectotérmicos. Em vertebrados ectotérmicos é comum que os animais apresentem uma preferência por uma determinada temperatura ou faixa de temperatura, a qual é chamada de temperatura corpórea preferida (Tpref). Essa preferência, porém, pode ser alterada em função de fatores externos ou da condição dos animais. Por exemplo, animais alimentados geralmente exibem um aumento da Tpref - referido como resposta termofilica pós-prandial - o que potencialmente melhora o desempenho da digestão do alimento. Esta resposta é relativamente bem documentada em Squamata, porém, dentre os anfíbios anuros, são escassas as informações sobre sua ocorrência, magnitude e possíveis determinantes. Desta forma, no presente estudo, nós investigamos se o sapo cururu, Rhinella diptycha, altera sua preferência térmica após terem sido alimentados com presa de massa equivalente a 15% de sua massa corpórea. Para tanto, animais alimentados e em jejum foram mantidos por oito dias consecutivos em gradiente térmico com temperaturas variando de 15ºC a 30ºC. Durante este periodo, a Tc dos sapos foi continuamente monitorada com sensores de temperatura (iButtons®) implantados intraperitonealmente. Os valores de Tpref dos animais alimentados aumentou para níveis significativamente maiores do que os valores de Tpref dos animais em jejum no segundo dia após a alimentação e essa diferença se manteve até o final dos experimentos. A ocorrência de uma resposta termofilica pós-prandial em...
Keywords: Sapos; Animais - Comportamento; Anuro; Anfíbio - Fisiologia; Temperatura corporal - Regulação; Digestão